2011
DOI: 10.1097/sap.0b013e3181f9b245
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Safety and Efficacy of Combined Abdominoplasty and Gynecologic Surgery

Abstract: These results demonstrate success in performing abdominoplasty with gynecologic surgery, which may be an acceptable option for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…One study discouraged ABP combined with cesarean delivery due to increased complications and unsatisfactory aesthetic outcomes [17]. More recently, most groups believe that a combined ABP-HYS is safe and does not have any increase in complication rates when compared to ABP and HYS on separate dates [1,[6][7][8][9][10]. One study even showed that concurrent ABP and panniculectomy with pelvic surgery in the morbidly obese had a lower incidence of wound infection and blood loss than pelvic surgery alone [18].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One study discouraged ABP combined with cesarean delivery due to increased complications and unsatisfactory aesthetic outcomes [17]. More recently, most groups believe that a combined ABP-HYS is safe and does not have any increase in complication rates when compared to ABP and HYS on separate dates [1,[6][7][8][9][10]. One study even showed that concurrent ABP and panniculectomy with pelvic surgery in the morbidly obese had a lower incidence of wound infection and blood loss than pelvic surgery alone [18].…”
Section: Discussionmentioning
confidence: 95%
“…Certain groups have reported that the combined procedure resulted in increased complications, particularly in an increased incidence of pulmonary embolus [2][3][4][5]. More recently, others have indicated that ABP-HYS is safe and does not result in an increase in complication rates when compared to ABP and HYS on separate dates [1,[6][7][8][9][10]. Additionally, it has been shown that the combined procedure can allow greater operative exposure, thus aiding the gynecologic surgeon [11].…”
Section: Introductionmentioning
confidence: 93%
“…The rate varies from 0.1% to 42%. [12] Seromas are distinctly more common in traditional abdominoplasty and distinctly less common in lipoabdominoplasty. [13] The earlier reports suggested that addition of liposuction increased the seroma rates, however in these series, the abdominoplasty was still done with full undermining to the rib cage.…”
Section: Discussionmentioning
confidence: 99%
“…There were no deep space infections or wound dehiscences (8). More recently, a case-control study compared patients undergoing combined abdominoplasty and gynecological surgery with individuals undergoing abdominoplasty alone and gynecological surgery alone (9). The combined group experienced no increased complications and, actually, when compared with the sum of procedures when performed alone, there were significant reductions in operative times, estimated blood loss and total length of hospitalization.…”
Section: Discussionmentioning
confidence: 99%